Repentance According To The Islamic And Christian Community Of Tembung Village, Percut Sei Tuan District - Kamaluddin, Kamaluddin; Fitriani, Fitriani; Pramudya, Rio (JURNAL JAWI, 2022)
Tembung Village is a village that has many Muslim and Christian religious figures. Tembung village is very active on religious matters, there are many religious activities held. But there are still bad behaviors committed by villagers, such as stealing, gambling, drugs, and so on. So that this behavior makes the community think that religious leaders have not succeeded in directing them to the right path and need to increase people's religious understanding, especially regarding repentance. Thus the authors are interested in conducting this research to find out how religious and community leaders interpret the term Taubat in religion. The research method used in this study is a qualitative method of the Field Research type with the Phenomenology of Religion approach using symbolic interaction theory. The results of the research that has been carried out show that the views of Muslim and Christian religious leaders in Tembung Village regarding repentance agree that it is obligatory for Muslims and Christians, whether male or female, as explained in the Al-Qur'an surah An-Nur verse 31 and Bible Matthew 4 verse 17. Every soul will surely die. To meet God, of course, humans must be clean and pure inside, of course, the best way to purify the mind is through repentance.